An Overview on Identifying Faults in 1-Phase Electrical System: DOI: 10.56815/IJEMS.V3.I1.2023/46-52 (International Journal of Engineering Management Science, 2023)
Wireless technology has found significant application in both industrial and home settings. The main goal is to transfer power wirelessly between the transmitting and receiving coils in the near field through resonant inductive coupling. Thus, we created a wireless solar-powered charging station for electric bicycles. High efficiency is required to verify optimal charging, which lowers energy losses. The RFID tag technology scans the individual bikes and permits charging in areas where unauthorized users have been warned or forbidden. This is frequently tracked and managed using a mobile app. It is more necessary to have a flexible wireless charging station for electric cycles in order to achieve wireless power transfer through inductive coupling. A charging station is essential for increased portability, mobility, and reduced infrastructure costs due to the absence of wires. Thus, an affordable electric cycle charging station has been built.
Keywords: Cyber security, electric vehicles, RFID, electric vehicle charging stations, smart grids.